2019
DOI: 10.1186/s12909-019-1593-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the critical thinking disposition inventory for Chinese medical college students (CTDI-M)

Abstract: Background This study aimed to develop and conduct psychometric testing of the Critical Thinking Disposition Inventory to measure the critical thinking disposition of Chinese medical college students. Methods The study was conducted in two stages: (a) item generation, reliability analysis and exploratory factor analysis (EFA) and (b) confirmatory factor analysis (CFA) and testing of psychometric properties (Cronbach’ s alpha, test-retest reliability and convergent valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…The low scores were consistent with findings by Kim & Choi (2014) and Hussein Ibrahim (2016), where objectivity score was 2.68±0.64 and 33.2±0.4 respectively due to reluctance to re-assess new knowledge. The truth-seeking result is consistent with Wang et al, (2018) where low scores (3.73±0.57) were also reported as compared with medical students. It was said to be related to individual confidence level.…”
Section: Level Of Critical Thinking Abilitysupporting
confidence: 86%
“…The low scores were consistent with findings by Kim & Choi (2014) and Hussein Ibrahim (2016), where objectivity score was 2.68±0.64 and 33.2±0.4 respectively due to reluctance to re-assess new knowledge. The truth-seeking result is consistent with Wang et al, (2018) where low scores (3.73±0.57) were also reported as compared with medical students. It was said to be related to individual confidence level.…”
Section: Level Of Critical Thinking Abilitysupporting
confidence: 86%
“…Studies on developing critical thinking disposition instruments have been carried out by several researchers [16,17,18]. Hwang et al developed scales of critical thinking dispositions [16].…”
Section: B Discussionmentioning
confidence: 99%
“…The results of the validity and reliability analysis showed that this inventory was valid and reliable to measure the students' critical thinking dispositions. On the other hand, Wang et al [18] have developed and validated an inventory of critical thinking dispositions for medical students in China. They found three subscales of critical thinking dispositions based on explanatory factor analysis, namely open-mindedness, systematicity/analyticity, and truth-seeking.…”
Section: B Discussionmentioning
confidence: 99%
“…Few students analyze and use critical thinking when they acquire knowledge during their education [6]. Therefore, critical thinking skills are increasingly necessary for medical students and professionals [7].…”
mentioning
confidence: 99%
“…A disposition to critical thinking is essential for professional clinical judgement [17]. An assessment of critical thinking disposition (CTD) in professional judgment circumstances and educational contexts can establish benchmarks to advance critical thinking through training programs [7]. To investigate and assess critical thinking in medical students, a reliable and valid tool is indispensable.…”
mentioning
confidence: 99%